ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN PETANI KARET MENJUAL BOKAR KE PENGEPUL DI DESA TANJUNG DAYANG KECAMATAN INDRALAYA SELATAN - Herlangga, Arya; Iskandar, Sutarmo (Universitas Muhammadiyah Palembang, 2024)
ABSTRACTThe aim of this research is to determine the factors that influence farmers' decisions to sell bokar to collector agents and to determine the profits of collector I and collector II in Tanjung Dayang Village, South Indralaya District. The research method used in this research is the survey method. The sampling method that will be used in this research is proportionate stratified random sampling and purposive sampling. The respondents in this study were 100 respondents with details of 69 respondents who sold bokar to collector I and 31 respondents who sold bokar to collector II. The data collection methods used are observation, interviews and documentation. The data processing methods used are editing, coding and tabulating. The research results show that the factors of age, education level, land area, family relationships and payment techniques simultaneously have a real influence on farmers' decisions to sell bokar to collector I or collector II in Tanjung Dayang Village, South Indralaya District. a) Age has no significant influence on the farmer's decision to sell bokar to collector I or collector II in Tanjung Dayang Village, South Indralaya District, b) Level of education has no significant influence on the farmer's decision to sell bokar to collector I or collector II in Tanjung Dayang Village, South Indralaya District , c) Land area has no real influence on the farmer's decision to sell bokar to collector I or collector II in Tanjung Dayang Village, South Indralaya District, d) Family relationships have a significant influence on the farmer's decision to sell bokar to collector I or collector II in Tanjung Dayang Village, Indralaya District South, and e) Payment techniques have a real influence on the farmer's decision to sell bokar to collector I or dealer II in Tanjung Dayang Village, South Indralaya District. Profits obtained by collectors I and II in purchasing bokar from rubber farmers in Tanjung Dayang Village, South Indralaya District, where the collector I owns the profits obtained by collectors I and II. Collector I has a profit of Rp. 20,514,611/Month and collector II Rp. 10,864,343/Month ABSTRAKTujuan penelitian ini adalah untuk mengetahui faktor yang mempengaruhi keputusan petani menjual bokar ke pengepul dan Untuk mengetahui besar keuntungan pengepul I dan pengepul II di Desa Tanjung Dayang Kecamatan Indralaya Selatan. Metode penelitian yang digunakan dalam penelitian ini adalah metode survei. Metode penarikan contoh yang akan digunakan dalam penelitian ini proportionate stratified random sampling dan purposive sampling. Responden dalam penelitian ini adalah 100 responden dengan rincian 69 responden yang mnjual bokar ke pengepul I dan 31 responden yang menjual bokar ke pengepul II. Metode pengumpulan data yang di gunakan adalah observasi, wawancara dan dokumentasi. Metode pengolahan data yang digunakan adalah editing, coding dan tabulating. Hasil penelitian menunjukan faktor umur, tingkat pendidikan, luas lahan, hubungan keluarga, dan teknis pembayaran secara simultan berpengaruh nyata terhadap keputusan petani menjual bokar ke pengepul I atau pengepul II di Desa Tanjung Dayang Kecamatan Indralaya Selatan. a) Umur berpengaruh tidak nyata terhadap keputusan petani menjual bokar ke pengepul I atau pengeul II di Desa Tanjung Dayang Kecamatan Indralaya Selatan, b) Tingkat pendidikan berpengaruh tidak nyata terhadap keputusan petani menjual bokar ke pengepul I atau pengeul II di Desa Tanjung Dayang Kecamatan Indralaya Selatan, c) Luas lahan berpengaruh tidak nyata terhadap keputusan petani menjual bokar ke pengepul I atau pengeul II di Desa Tanjung Dayang Kecamatan Indralaya Selatan, d) Hubungan keluarga berpengaruh nyata terhadap keputusan petani menjual bokar ke pengepul I atau pengeul II di Desa Tanjung Dayang Kecamatan Indralaya Selatan, dan e)Teknis pembayaran berpengaruh nyata terhadap keputusan petani menjual bokar ke pengepul I atau pengeul II di Desa Tanjung Dayang Kecamatan Indralaya Selatan Keuntungan yang diperoleh pengepul I dan II dalam melakukan pembelian bokar petani karet di Desa Tanjung Dayang Kecamatan Indralaya Selatan, dimana pengepul I meliliki keuntungan yang di dapatkan oleh pengepul I dan II. Pada pengepul I memilki keuntungan sebesar Rp. 20.514.611/Bulan dan pengepul II Rp. 10.864.343/Bulan